PENGARUH STRATEGI DISKUSI DAN STRATEGI EKSPOSITORI TERHADAP HASIL BELAJAR MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA SISWA KELAS VIII MTs AL-ULUM MEDAN KECAMATAN MEDAN AREA TAHUN PEMBELAJARAN 2021-2022 - Parianto, M. Hadi Rizal, Zulkarnaen Guchi (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
This study aims to determine the learning outcomes of Islamic Cultural History using discussion and expository strategies as well as the influence of discussion strategies on learning outcomes of Islamic Cultural History in Grade VIII Students of MTs Al-Ulum Medan, Medan Area District, for the 2021-2022 academic year. The population of all class VIII students totaled 195 students. The sample was determined purposively, namely 24 students in class VIII.1 as the experimental group and 24 students in class VIII.2 as the control group. The purpose of this study was to find out how the learning outcomes of Islamic cultural history used the discussion strategy for class VIII students of MTs Al-Ulum Medan, Medan District in the year 2021-2022 and to find out how the learning outcomes of Islamic cultural history used the expository strategy for class VIII students of MTs Al- Ulum Medan District of Medan Area for the 2021-2022 academic year. This study used an experimental method, with a test instrument for Islamic Cultural History learning outcomes in the form of multiple choice objectives of 25 questions. This test was tested after each group participated in learning using discussion and expository strategies. Because this research is comparative in nature, the average value of variable X1 and variable X2 is compared to one another. The comparison used is the t-test statistic, namely the test of the difference in the mean of two independent sample groups. Based on the results of data analysis and statistical tests, it was concluded from the results of the study: The learning outcomes of Islamic Cultural History using the discussion strategy obtained an average value of 84.5. The acquisition of the average value indicates that the group of students who were taught using the discussion strategy has the learning outcomes category A (very good). The learning outcomes of Islamic Cultural History using the Expository strategy obtained an average value of 75.8. The acquisition of the average value indicates that the group of students who are taught using the Expository strategy has a learning outcome category B (good). Learning with a discussion strategy has a significant influence on the learning outcomes of Islamic Cultural History for class VIII MTs Al-Ulum Medan. This is evidenced by calculations using the "t" test, where the t calculation results are compared with ttable and obtained tcount ttable or 4.37 1.677.